Web-based system for assessing risk factors for falls in community-dwelling elderly people using the Analytic Hierarchy Process - Pecchia, Leandro; Bath, Peter A.; Pendleton, Neil; Bracale, Marcello (Creative Decisions Foundation (CDF), 2010)
Falls occur frequently among older people and represent the most common cause of injury-related morbidity and mortality in later life. Preventing falls is an important way to reduce injuries, hospitalizations, and injury-related morbidity and mortality among older people. The research literature has identified hundreds of risk factors for falls among elderly people. Prioritizing risk factors for falls is useful for designing effective and efficacious prevention programs. The aim of this study was to use the Analytic Hierarchy Process to develop a hierarchy of risk factors for falls based on the knowledge and experience of experts working in this field.